Odpowiedzi

2010-02-16T18:26:56+01:00
A) 4 razy (0,5 ) ² + 6 razy ( -dwie trzecie) ² = 4 * 0,25 + 6 * 4/6 = 1 + 4 = 5

b) ( jedna druga ) ² + (0,8) : (-cztery piąte) = 1/4 + 0,8 : (-0,8) = 1/4 + (-1) = -3/4

c) dwie trzecie + [(-jedna trzecia)² + (- jedna trzecia)²]:jedna trzecia
= 2/3 + [(-1/9 + (-1/9)] = 2/3 + (-2/9) = 6/9 + (-2/9) = 4/9
2010-02-16T18:34:18+01:00
A) 4 razy (0,5 ) ² + 6 razy ( -dwie trzecie) ²=-5/3
b) ( jedna druga ) ² + (0,8) : (-cztery piąte) =-3/4
c) dwie trzecie + [(-jedna trzecia)² + (- jedna trzecia)²]:jedna trzecia =1/2